Análisis de deformaciones en soportes de túneles construidos en suelos arcillosos saturados bajo condiciones drenadas (2020)
In civil engineering, the modeling of real situations through analog models and specialized analysis software is of vital importance. The centrifugal machine is a tool that allows modeling soils at a specific gravity in order to expose their behavior over time. At the same time, it allows to recreate real life conditions (prototypes), in scale structures with much smaller dimensions (model). This work seeks to analyze the behavior of tunnel supports built in saturated clay soils under drained conditions in a stratified soil model subjected to an acceleration of 80 gravities. For this, an analysis will be carried out under non-drained conditions, under saturated conditions and another under drained conditions. The analysis will be carried out through two means. The first will be through deformation sensors to measure settlements and a piezometer to measure the water table throughout the test. The second through image analysis performed with software specialized in the analysis of particle motion in Matlab. Through image analysis, the aim is to identify the direction of the displacements of the model particles during centrifugal flights and to quantify their magnitude. In addition, it seeks to observe the behavior of the kaolin layer at different times of flight and under different water levels. The behavior of a clay soil under drained and undrained conditions determines that it works with total efforts or effective efforts, depending on the pore pressure provided by the effect of water on the clay. In the analysis, this effect and its evolution over time will be taken into account.